37.4k views
1 vote
Pls solve the above question
Kindly don't spam+_+​

Pls solve the above question Kindly don't spam+_+​-example-1
User MoreON
by
5.4k points

1 Answer

2 votes

Answer:

Explanation:

Given expressions are,


p=(√(10)-√(5))/(√(10)+√(5)) and
q=(√(10)+√(5))/(√(10)-√(5))

Remove the radicals from the denominator from both the expressions.


p=(√(10)-√(5))/(√(10)+√(5)) * (√(10)-√(5))/(√(10)-√(5))


=((√(10)-√(5))^2)/((√(10))^2-(√(5))^2)


=((√(10)-√(5))^2)/(5)


√(p)=\sqrt{((√(10)-√(5))^2)/(5)}


=(√(10)-√(5))/(√(5))


q=(√(10)+√(5))/(√(10)-√(5))


=(√(10)+√(5))/(√(10)-√(5))* (√(10)+√(5))/(√(10)+√(5))


=((√(10)+√(5))^2)/((√(10))^2-(√(5))^2)


=((√(10)+√(5))^2)/(5)


√(q)=\sqrt{((√(10)+√(5))^2)/(5)}


=((√(10)+√(5)))/(√(5))


√(q)-√(p)-2√(pq)=((√(10)+√(5)))/(√(5))-((√(10)-√(5)))/(√(5))-2(((√(10)+√(5)))/(√(5)))(((√(10)-√(5)))/(√(5)))


=(1)/(√(5))(√(10)+√(5)-√(10)+√(5))-(2)/(5)[(√(10))^2-(√(5))^2)]


=(1)/(√(5))(2√(5))-(2)/(5)(10-5)


=2-2


=0

User Randalv
by
4.3k points